The Moon Scroll - Abbott, Tony, 1952-; Jessell, Tim (New York : Scholastic, 2002)
In order to defend himself in Lord Sparr's evil underworld, Galen needs the powerful wand of Urik, a magic tool that's been hidden for years. Keeah and her Upper World friends attempt to find the wand by following the Moon Scroll, which has the power to take anyone who reads it back through time.
"A Little Apple paperback."
G2
Keywords: Magic -- Fiction; Time travel -- Fiction; Fantasy